Heat insulation element and battery

By using a heat insulation layer composed of chopped fibers, thermal insulation powder and heat absorption materials in the power battery, the problem of heat transfer and spread after thermal runaway of the battery cell is solved, and higher battery safety is achieved.

CN119447620APending Publication Date: 2025-02-14GONG YI VAN RES INNOVATION COMPOSITE MATERIAL CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202310969561.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-02
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

In power batteries, the battery cell has heat out of control and heat out of control, causing safety accidents.

Method used

Provided is a heat insulation element, including a heat insulation layer, which consists of chopped fibers, heat insulation powder and heat absorbing material. The thickness of the heat insulation layer is ≤10mm, and the thermal conductivity is ≤0.04W/(m· K) and 500°C ≤0.06W/(m·K) to prevent heat transfer and delay thermal runaway spread.

Benefits of technology

Effectively prevent heat transfer between battery cells and between battery cells and the housing, delay thermal runaway spread, and improve battery safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119447620A_ABST
    Figure CN119447620A_ABST
Patent Text Reader

Abstract

The invention provides a heat insulation element and a battery, the heat insulation element comprises a heat insulation layer, the heat insulation layer comprises chopped fibers and heat insulation powder, the thickness of the heat insulation layer is less than or equal to 10mm, the heat conductivity coefficient of the heat insulation layer at 25 DEG C is less than or equal to 0.04 W / (m.K), and the heat conductivity coefficient of the heat insulation layer at 500 DEG C is less than or equal to 0.06 W / (m.K). The heat insulation element can prevent heat transfer between the battery monomers or heat transfer from the battery monomers to the battery shell under a low-temperature condition, and can prevent the battery monomers from transferring heat to the adjacent battery monomers or the battery shell when the battery monomers have a battery swelling stage or a thermal runaway stage, so that the spreading of the thermal runaway of the battery is effectively delayed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of power batteries, and in particular to a heat insulation element and a battery. Background Art

[0002] For new energy vehicles, power battery technology is an important factor related to their development. With the rapid development of electric vehicles, the safety issues of electric vehicle power battery systems have restricted the rapid development of electric vehicles.

[0003] The battery includes a battery module and multiple battery cells in the battery module that are connected in series and / or in parallel. The battery cell is the smallest unit in the battery that provides energy. Safety accidents of electric vehicle power batteries are mainly characterized by the spread of thermal runaway of the battery module. After the thermal runaway of the power battery cell, the high temperature will be quickly transferred to the adjacent cells, causing chain thermal runaway to spread, resulting in safety accidents such as fire and explosion, which seriously threatens the safety of people and property. Summary of the invention

[0004] The heat insulation element and battery provided in the present application are intended to solve the problem in existing power batteries that thermal runaway occurs after thermal runaway of battery cells, causing the spread of thermal runaway.

[0005] In order to solve the above technical problems, a technical solution adopted in the present application is: to provide a thermal insulation element, including a thermal insulation layer, the thermal insulation layer includes chopped fibers and thermal insulation powder, the thickness of the thermal insulation layer is ≤10mm, the thermal conductivity of the thermal insulation layer at 25°C is ≤0.04W / (m·K), and the thermal conductivity of the thermal insulation layer at 500°C is ≤0.06W / (m·K).

[0006] In a specific embodiment, the heat insulation layer further includes a heat absorbing material, and the heat absorbing material is evenly dispersed in the gaps and / or surfaces of the chopped fibers and the gaps and / or surfaces of the heat insulation powder.

[0007] In a specific embodiment, the endothermic material can undergo an endothermic reaction after reaching an endothermic reaction starting temperature, and the endothermic reaction starting temperature is 70°C-300°C.

[0008] In a specific embodiment, the endothermic material is capable of undergoing volume loss and gas volatilization during the endothermic reaction.

[0009] In a specific embodiment, after the endothermic reaction of the endothermic material occurs, the porosity of the heat insulating layer is 10%-80%, and the density of the heat insulating layer is 0.9 g / cm 3 -2.5g / cm 3 .

[0010] In a specific embodiment, the volume of the heat absorbing material accounts for ≤80% of the total volume of the chopped fibers, the thermal insulation powder and the heat absorbing material.

[0011] In a specific embodiment, the endothermic material includes a phase change material and / or two or more materials capable of undergoing an endothermic reduction reaction.

[0012] In a specific embodiment, the phase change material includes an inorganic phase change material and / or an organic phase change material; preferably, the inorganic phase change material includes one or more of inorganic hydrated salts, carbonates, bicarbonates, and hydroxides; preferably, the inorganic phase change material includes one or more of sodium bicarbonate, ammonium aluminum sulfate dodecahydrate, magnesite, calcium sulfate dihydrate, potassium carbonate, aluminum hydroxide, aluminum oxide hydroxide, and magnesium hydroxide; preferably, the organic phase change material includes one or more of paraffin, fatty acids, and fatty alcohols.

[0013] In a specific embodiment, the two or more materials capable of undergoing endothermic reduction reaction include iron oxide and activated carbon and a sodium carbonate catalyst.

[0014] In a specific embodiment, the heat insulation layer is obtained by uniformly mixing the chopped fibers, the heat insulation powder and the heat absorbing material and then pressing and molding the mixture.

[0015] In a specific embodiment, the heat insulation layer further includes a flame retardant and / or a sunscreen.

[0016] In a specific embodiment, the heat insulation element further includes a heat absorption layer, and the heat absorption layer is disposed on at least one surface of two opposite surfaces of the heat insulation layer.

[0017] In a specific embodiment, the thermal insulation element further includes a packaging layer, and the packaging layer covers the thermal insulation layer or covers the thermal insulation layer and the heat absorption layer.

[0018] In order to solve the above technical problems, another technical solution adopted by the present application is to provide a battery, comprising:

[0019] case;

[0020] One or more battery cells disposed within the housing;

[0021] Thermal insulation elements as mentioned in any of the above;

[0022] The heat insulating element is arranged between adjacent battery cells, and / or the heat insulating element is arranged between the battery cells and the housing.

[0023] In a specific embodiment, the battery further comprises an exhaust valve and / or a liquid discharge valve, and the exhaust valve and / or the liquid discharge valve are connected to the thermal insulation element.

[0024] Beneficial effects of the embodiments of the present application: Different from the prior art, the present application provides a thermal insulation element and a battery, wherein the thermal insulation element includes a thermal insulation layer, the thermal insulation layer includes chopped fibers and thermal insulation powder, and the thickness of the thermal insulation layer is ≤10mm to meet the requirements of high energy density and high volume assembly rate of the battery; the thermal conductivity of the thermal insulation layer at 25°C is ≤0.04W / (m·K) to prevent heat transfer between battery cells or heat transfer from battery cells to battery casings; the thermal conductivity of the thermal insulation layer at 500°C is ≤0.06W / (m·K) to prevent a battery cell from transferring heat to adjacent battery cells or battery casings when a battery bulging stage or thermal runaway stage occurs in the battery cell, thereby effectively delaying the spread of thermal runaway of the battery. In addition, compared with the prior art that uses long fibers as reinforcing fibers, the present application uses shorter chopped fibers as reinforcing fibers, which is beneficial to the uniform mixing of the reinforcing fibers and the insulation powder, thereby improving the insulation performance of the insulation element; at the same time, the chopped fibers can also provide mechanical reinforcement for the insulation powder, so that the insulation element made of the chopped fibers and the insulation powder has a certain molding strength. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 A schematic diagram of the structure of a heat insulation element provided in one embodiment of the present application;

[0026] Figure 2 A schematic structural diagram of a heat insulation element provided in another embodiment of the present application;

[0027] Figure 3 A schematic diagram of the structure of a heat insulation element provided in one embodiment of the present application;

[0028] Figure 4 A simplified structural diagram of a battery provided in one embodiment of the present application.

[0029] Description of Figure Numbers:

[0030] 1- thermal insulation element; 2- battery cell; 3- shell; 11- thermal insulation layer; 12- heat absorption layer; 13- packaging layer; 101- short-cut fiber; 102- thermal insulation powder; 103- heat absorption material. DETAILED DESCRIPTION

[0031] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0032] The terms "first", "second", "third" in this application are only used for descriptive purposes, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of indicated technical features. Thus, the features defined as "first", "second", "third" can expressly or implicitly include at least one of the features. In the description of this application, the meaning of "multiple" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined. In the embodiments of this application, all directional indications (such as up, down, left, right, front, back...) are only used to explain the relative position relationship, movement, etc. between the components under a certain specific posture (as shown in the accompanying drawings). If the specific posture changes, the directional indication also changes accordingly. In addition, the terms "including" and "having" and any of their variations are intended to cover non-exclusive inclusions. For example, a process, method, system, product or device comprising a series of steps or units is not limited to the steps or units listed, but optionally also includes steps or units that are not listed, or optionally also includes other steps or units inherent to these processes, methods, products or devices.

[0033] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0034] In the relevant technology, the safety accidents of electric vehicle power batteries are mainly characterized by the spread of thermal runaway of battery modules. The thermal runaway of battery cells is caused by the fact that the heat generation rate of battery cells is much higher than the heat dissipation rate, and a large amount of heat is accumulated but not dissipated to the outside of the battery cells in time. After the thermal runaway of the power battery cell, the high temperature will be quickly transferred to the adjacent cells, causing the chain thermal runaway to spread, resulting in safety accidents such as fire and explosion, which seriously threatens the safety of people and property.

[0035] Based on this, an embodiment of the present application provides a thermal insulation element and a battery, which can prevent heat transfer between battery cells or heat transfer from battery cells to battery casings under low temperature conditions, and can prevent a battery cell from transferring heat to adjacent battery cells or battery casings when a battery cell is in a battery bulging stage or a thermal runaway stage, thereby effectively delaying the spread of battery thermal runaway.

[0036] The present application is described in detail below with reference to the accompanying drawings and embodiments.

[0037] The present application provides a thermal insulation element 1, which can be applied to, but not limited to, power batteries to isolate heat transfer inside the power batteries. Specifically, the thermal insulation element 1 may include a thermal insulation layer 11; in some embodiments, the thermal insulation layer 11 may include chopped fibers 101 and thermal insulation powder 102. The chopped fibers 101 are used as reinforcing fibers to enhance the mechanical strength of the thermal insulation element 1; the thermal insulation powder 102 is evenly distributed on the surface of the chopped fibers 101 and in the fiber gaps to enhance the thermal insulation performance of the thermal insulation layer 11. Figure 1 This is only a schematic diagram. In the actual product, the chopped fibers 101 are basically randomly distributed.

[0038] In these embodiments, the thickness of the thermal insulation layer 11 is ≤10 mm. For example, the thickness of the thermal insulation layer 11 can be 1 mm, 3 mm, 5 mm, 8 mm, or 10 mm, so that the thermal insulation element 1 is as thin as possible while having excellent thermal insulation performance, thereby meeting the increasing requirements of high energy density and high volume assembly rate of power batteries.

[0039] On the other hand, the thermal conductivity of the thermal insulation layer 11 at 25°C is ≤0.04W / (m·K); for example, the thermal conductivity of the thermal insulation layer 11 at 25°C may be 0.02W / (m·K), 0.03W / (m·K), or 0.04W / (m·K) to prevent heat transfer between battery cells 2 or heat transfer from battery cells 2 to battery housing 3. At the same time, the thermal conductivity of the thermal insulation layer 11 at 500°C is ≤0.06W / (m·K); for example, the thermal conductivity of the thermal insulation layer 11 at 500°C may be 0.03W / (m·K), 0.05W / (m·K), or 0.06W / (m·K) to prevent a battery cell 2 from transferring heat to an adjacent battery cell 2 or battery housing 3 when a battery bulge or thermal runaway occurs, thereby effectively delaying the spread of thermal runaway of the battery.

[0040] In addition, compared with the prior art that uses long fibers as reinforcing fibers, the present application uses shorter chopped fibers 101 as reinforcing fibers, which is beneficial to the uniform mixing of the reinforcing fibers and the insulating powder 102, thereby improving the thermal insulation performance of the insulating element 1; at the same time, the chopped fibers 101 can also provide mechanical reinforcement for the insulating powder 102, so that the insulating element 1 made of the chopped fibers 101 and the insulating powder 102 has a certain molding strength to meet the application of the insulating element 1 between battery cells 2 or between battery cells 2 and the battery casing 3.

[0041] Specifically, a fracture test can be conducted in the laboratory to ensure that the molding strength of the thermal insulation element 1 meets the application requirements, as follows: the thermal insulation element 1 is made into a sample of 250mm*50mm*3mm, 250mm is defined as the length direction, one end of the sample in the length direction is placed on the test bench and the other end is suspended without the support of the test bench, the length of one end of the sample in the length direction placed on the test bench is 50mm, pressure is applied to the end placed on the test bench to prevent the thermal insulation element 1 from falling off the test bench, and the thermal insulation element 1 is not broken, that is, the molded sample meets the mechanical performance requirements for use in batteries. Preferably, the thermal insulation element 1 is made into a sample of 250mm*50mm*3mm, and when the fracture test is performed, after the thermal insulation element 1 sample sags, the height difference between the drooping end and the end on the test bench is ≤40mm.

[0042] See also Figure 1 , Figure 1 This is a schematic diagram of the structure of a heat insulation element provided in one embodiment of the present application. In a specific embodiment, Figure 1 As shown, the thermal insulation layer 11 may only include chopped fibers 101 and thermal insulation powder 102, and the thermal insulation layer 11 is obtained by uniformly mixing the chopped fibers 101 and the thermal insulation powder 102 and then pressing and molding. Preferably, the chopped fibers 101 and the thermal insulation powder 102 are mixed in a ratio of (1.5-40): (25-90) by mass; for example, the mass ratio of the chopped fibers 101 and the thermal insulation powder 102 is any value such as 5:40, 10:50, 20:60, 25:70, 40:80, etc. The content of the chopped fibers 101 ensures that the mechanical properties of the thermal insulation element 1 meet the application requirements without adversely affecting the thermal insulation performance of the thermal insulation element 1. The content of the thermal insulation powder 102 ensures that the thermal insulation performance of the thermal insulation element 1 meets the use requirements.

[0043] The chopped fibers 101 may include one or more of glass fibers, alumina fibers, and aluminum silicate fibers; in a specific embodiment, the diameter of the chopped fibers 101 is preferably 1-20 μm, and the length is preferably 4 mm-20 mm; for example, the diameter of the chopped fibers 101 may be 1 μm, 5 μm, 10 μm, 15 μm, 20 μm, and the length may be 4 mm, 8 mm, 12 mm, 16 mm, 20 mm, so as to make the chopped fibers 101 and the insulation powder 102 more evenly mixed, thereby improving the insulation performance and mechanical properties of the insulation element 1. It can be understood that in a specific embodiment, the diameter and length of the chopped fibers 101 may be any value within the preferred range, and they are different; that is, chopped fibers 101 of different diameters and lengths may exist in the insulation layer at the same time.

[0044] In a specific embodiment, the thermal insulation powder 102 includes nano thermal insulation powder and / or micron thermal insulation powder; wherein the particle size of the nano thermal insulation powder is preferably 5-100nm; for example, the particle size of the nano thermal insulation powder can be 5nm, 20nm, 50nm, 80nm, 100nm. It can be understood that nano thermal insulation powders of different particle sizes can exist in the thermal insulation layer at the same time. Specifically, the nano thermal insulation powder can include one or more of nano gas-phase silica powder, nano gas-phase alumina powder, nano zirconium oxide powder, nano titanium oxide powder, nano iron oxide powder, nano zirconium oxide aerogel powder, nano silica aerogel powder and nano alumina aerogel powder.

[0045] The particle size of the micron thermal insulation powder is preferably 1-100 μm; for example, the particle size of the nano thermal insulation powder can be 1 μm, 20 μm, 50 μm, 80 μm, 100 μm. It is understood that micron thermal insulation powders of different particle sizes can exist in the thermal insulation layer at the same time. Specifically, the micron thermal insulation powder can include one or more of micron fumed alumina powder, micron fumed silica powder, silica ash, white carbon black, diatomaceous earth, fly ash, micron alumina aerogel powder and micron silica aerogel powder.

[0046] In some embodiments, the thermal insulation powder 102 may be a nano thermal insulation powder or a mixture of multiple nano thermal insulation powders; or, the thermal insulation powder 102 may be a micron thermal insulation powder or a mixture of multiple micron thermal insulation powders; or, the thermal insulation powder 102 may be a mixture of nano thermal insulation powder and micron thermal insulation powder; the thermal insulation powder 102 of corresponding composition may be selected according to the thermal insulation performance requirements of the thermal insulation element 1. In these embodiments, the thermal conductivity of the thermal insulation layer 11 at 25°C is ≤0.018W / (m·K), and the thermal conductivity of the thermal insulation layer 11 at 500°C is ≤0.024W / (m·K); for example, the thermal conductivity of the thermal insulation layer 11 at 25°C may be 0.17W / (m·K) or 0.018W / (m·K), and the thermal conductivity of the thermal insulation layer 11 at 500°C may be 0.022W / (m·K) or 0.024W / (m·K).

[0047] See also Figure 2 , Figure 2A schematic diagram of the structure of a thermal insulation element provided in another embodiment of the present application. The structure of the thermal insulation element 1 provided in this embodiment is basically the same as that of the thermal insulation element 1 provided in the above-mentioned embodiment of the present application, except that, in this embodiment, the thermal insulation layer 11 may also include a heat-absorbing material 103, and the thermal insulation layer 11 is obtained by evenly mixing the chopped fibers 101, the thermal insulation powder 102 and the heat-absorbing material 103 and then pressing and molding them, so that the performance of the thermal insulation layer 11 can be kept consistent everywhere. Among them, the heat-absorbing material 103 is evenly dispersed in the gaps and / or surfaces of the chopped fibers 101 and the gaps and / or surfaces of the thermal insulation powder 102 to absorb the heat of the battery cells 2, which can effectively avoid thermal runaway of the battery cells 2, and can delay the spread of the battery cells 2 to adjacent battery cells 2 or the battery casing 3 when the battery cells 2 are in thermal runaway.

[0048] Specifically, the endothermic material 103 can undergo an endothermic reaction to absorb the heat generated by the battery cell 2. After the temperature of the battery cell 2 rises to the starting temperature of the endothermic reaction, the endothermic material 103 can undergo an endothermic reaction, and the starting temperature of the endothermic reaction is 70°C-300°C; for example, the starting temperature of the endothermic reaction can be 70°C, 100°C, 150°C, 200°C, 300°C, and the specific starting temperature is determined by the chemical properties of the selected endothermic material 103 itself. In this way, the endothermic material 103 can absorb heat before the battery cell 2 starts to have thermal runaway to complete thermal runaway, so as to reduce the transfer of heat to the adjacent battery cell 2 or the housing 3, and avoid further development of thermal runaway. In addition, by having the starting temperature of the endothermic reaction of the endothermic material 103 be 70°C-300°C, the endothermic material 103 can be prevented from reacting and failing at a lower temperature, so that it can better play its effect of absorbing heat at a higher temperature where thermal runaway occurs.

[0049] It can be understood that at room temperature (25°C), the low thermal conductivity of the insulation element 1 mainly depends on the insulation powder 102, and the thermal conductivity of the endothermic material 103 is higher than that of the insulation powder 102. However, since the endothermic material 103 is evenly dispersed between the fiber pores and the insulation powder 102, the endothermic material 103 does not form a continuous phase, and the solid-phase heat conduction between the endothermic materials 103 is suppressed; therefore, before the endothermic reaction occurs, the endothermic material 103 has little effect on the overall thermal conductivity of the insulation element 1.

[0050] Furthermore, the endothermic material 103 can also experience volume loss and gas volatilization during the endothermic reaction; as the endothermic reaction proceeds, the endothermic material 103 partially decomposes or volatilizes to form a gap between the chopped fibers 101 and the insulation powder 102, making the thermal conductivity of the insulation layer 11 better at high temperatures. Those skilled in the art can understand that at high temperatures (500°C), the lower the thermal conductivity of the insulation element 1, the better the effect of suppressing heat transfer from the battery cell 2 to the adjacent battery cell 2 or the battery housing 3 when the battery cell 2 has thermal runaway, and the longer the time to delay the spread of the battery thermal runaway.

[0051] Specifically, the volume of the heat-absorbing material 103 accounts for ≤80% of the total volume of the chopped fibers 101, the heat-insulating powder 102 and the heat-absorbing material 103; for example, the volume of the heat-absorbing material 103 may account for 10%, 30%, 50%, 60%, or 80%, so that the heat-absorbing material 103 can absorb enough heat when the heat-absorbing material 103 undergoes an endothermic reaction to delay the thermal runaway of the battery cell 2. Furthermore, after the heat-absorbing material 103 undergoes an endothermic reaction, the porosity of the heat-insulating layer 11 may be 10%-80%, and the density of the heat-insulating layer 11 may be 0.9 g / cm 3 -2.5g / cm 3 , so as to further reduce the thermal conductivity of the heat insulation layer 11 in the high temperature section and better achieve the high temperature heat insulation effect. For example, the porosity of the heat insulation layer 11 can be 10%, 30%, 50%, 60%, 80%, and the density of the heat insulation layer 11 can be 0.9g / cm 3 , 1.2g / cm 3 , 1.6g / cm 3 , 2.0g / cm 3 , 2.5g / cm 3 .

[0052] In a specific embodiment, the heat-absorbing material 103 may include a phase change material and / or two or more materials capable of undergoing an endothermic reduction reaction. The phase change material can change its physical state when the ambient temperature reaches the phase change temperature and absorb a large amount of heat during the phase change process; and the two or more materials capable of undergoing an endothermic reduction reaction undergo a chemical reduction reaction between the materials when the ambient temperature reaches the reaction starting temperature to absorb the heat generated by the battery cell 2.

[0053] Specifically, the phase change material may include an inorganic phase change material and / or an organic phase change material. Among them, the inorganic phase change material may include one or more of inorganic hydrated salts, carbonates, bicarbonates, and hydroxides. When the battery expands thermally or thermally runs away, the inorganic phase change material undergoes an endothermic reaction when heated to produce moisture or volatile gas. The moisture can continue to absorb heat and then volatilize into gas to delay the spread of thermal runaway of the battery cell 2; and after the gas is removed, micropores can be formed between the chopped fibers 101 and the insulating powder 102 of the thermal insulation layer 11 to reduce the thermal conductivity of the high temperature section of the thermal insulation layer 11 and improve the thermal insulation performance of the thermal insulation element 1. Preferably, the inorganic phase change material may include one or more of sodium bicarbonate, ammonium aluminum sulfate dodecahydrate, magnesite, calcium sulfate dihydrate, potassium carbonate, aluminum hydroxide, aluminum oxide hydroxide, and magnesium hydroxide.

[0054] The organic phase change material may include one or more of paraffin, fatty acid, and fatty alcohol. The organic phase change material can be melted and solidified multiple times without phase separation, so that the heat absorbing material 103 can be reused, reducing the use cost; and the organic phase change material is generally non-corrosive, which can avoid corrosion to the heat insulation element 1 or the battery and the housing 3, thereby improving the safety of the battery.

[0055] The two or more materials capable of undergoing endothermic reduction reactions may include iron oxide, activated carbon and sodium carbonate catalyst. Among them, iron oxide and activated carbon can undergo redox reactions in a high temperature environment and absorb the heat generated by the battery cell 2 during the reaction; the sodium carbonate catalyst can reduce the starting temperature of the reaction of iron oxide and activated carbon to about 200°C, and the sodium carbonate catalyst has little effect on the endothermic enthalpy per unit mass of iron oxide and activated carbon. The products of the redox reaction of iron oxide and activated carbon are iron tetroxide, ferrous oxide and iron, accompanied by carbon dioxide and a small amount of carbon monoxide. The reaction chemical equation is as follows: 3Fe2O3+1 / 2C→2Fe3O4+1 / 2CO2, Fe3O4+1 / 2C→3FeO+1 / 2CO2, 2FeO+C→2Fe+CO.

[0056] In the above embodiments, preferably, the thickness of the thermal insulation layer 11 is ≤3 mm, for example, the thickness of the thermal insulation layer 11 may be 1 mm, 1.5 mm, 2 mm, 2.5 mm, or 3 mm; more preferably, the thickness of the thermal insulation layer 11 is ≤1 mm, for example, the thickness of the thermal insulation layer 11 may be 0.1 mm, 0.3 mm, 0.5 mm, 0.8 mm, or 1 mm, so as to further improve the energy density and volume assembly rate of the power battery.

[0057] Hereinafter, the present invention will be described in more detail according to the following examples and test examples. However, the following examples and comparative examples are provided only for illustrating the present application, and the scope of the present application is not limited thereto.

[0058] Example 1

[0059] In this embodiment, the heat insulating layer 11 includes chopped fibers 101, heat insulating powder 102 and heat absorbing material 103. Among them, the chopped fibers 101 are preferably glass fibers with a diameter of 6-12 μm and a length of 4-10 mm, and the content of glass fibers is 20%; the heat insulating powder 102 is preferably fumed silica powder with a particle size distribution of 50-100 nm, and the content of fumed silica is 30%; the heat absorbing material 103 is preferably ammonium aluminum sulfate dodecahydrate, and its content is 50%. The glass fibers, fumed silica powder and ammonium aluminum sulfate dodecahydrate are uniformly mixed and pressed to obtain the heat insulating layer 11, and the various properties of the heat insulating layer 11 are tested, and the results are shown in Table 2.

[0060] Example 2

[0061] In this embodiment, the heat insulating layer 11 includes chopped fibers 101, heat insulating powder 102 and heat absorbing material 103. Among them, the chopped fibers 101 are preferably glass fibers with a diameter of 10-20 μm and a length of 10-20 mm, and the content of glass fibers is 5%; the heat insulating powder 102 is preferably fumed silica powder with a particle size of 50 nm, and the content of fumed silica is 70%; the heat absorbing material 103 is preferably paraffin, and the content is 25%. It should be noted that the paraffin in this embodiment is paraffin particles with a smaller particle size. The glass fibers, fumed silica powder and paraffin particles are mixed evenly and then pressed to form the heat insulating layer 11, and the various properties of the heat insulating layer 11 are tested, and the results are shown in Table 2.

[0062] Example 3

[0063] In this embodiment, the heat insulating layer 11 includes chopped fibers 101, heat insulating powder 102 and heat absorbing material 103. Among them, the chopped fibers 101 are preferably glass fibers with a diameter of 1-10 μm and a length of 10-15 mm, and the content of the glass fibers is 10%; the heat insulating powder 102 is preferably a combination of nano-fumed silica powder and micron silica ash, and the nano-fumed silica powder and micron silica ash are combined in a mass ratio of 60:40, the nano-fumed silica powder is preferably fumed silica powder with a particle size of 50-80 nm, the micron silica ash is preferably silica ash with a particle size of 1-50 μm, and the content of the nano-fumed silica powder and the micron silica ash is 50%; the heat absorbing material 103 is preferably iron oxide, activated carbon and sodium carbonate catalyst, and the content of the three is 40%. Glass fiber, nano-fumed silica powder, micron silica fume iron oxide, activated carbon and sodium carbonate catalyst were uniformly mixed and pressed to obtain a heat insulation layer 11. Various properties of the heat insulation layer 11 were tested, and the results are shown in Table 2.

[0064] Example 4

[0065] In this embodiment, the thermal insulation layer 11 includes chopped fibers 101 and thermal insulation powder 102. The chopped fibers 101 are preferably a combination of glass fibers and alumina fibers with a diameter of 10-20 μm and a length of 4-10 mm, the glass fibers and alumina fibers are combined in a weight ratio of 80:20, and the content of the chopped fibers is 40%; the thermal insulation powder 102 is preferably fumed silica powder with a particle size of 50-100 nm, and the content of fumed silica is 60%. The glass fibers, alumina fibers and fumed silica powder are uniformly mixed and pressed to obtain the thermal insulation layer 11, and the various properties of the thermal insulation layer 11 are tested, and the results are shown in Table 2.

[0066] Comparative Example 1

[0067] In comparative example 1, the heat insulating layer includes a fluffy glass fiber mesh and a heat insulating powder 102. The content of the fluffy fiber mesh is 60%, and the heat insulating powder 102 preferably comprises fumed silica powder having a particle size of 5-50 nm, and the content of the fumed silica is 40%. The fumed silica powder is spread on the surface of the fluffy fiber mesh in batches and then pressed, and the fumed silica powder is pressed into the fluffy fiber mesh to obtain a heat insulating layer 11, and various properties of the heat insulating layer 11 are tested, and the results are shown in Table 2.

[0068] Comparative Example 2

[0069] In Comparative Example 2, silica sol and glass fiber mat made of glass fiber are compounded by sol-gel method, and then silica sol is gelled to form silica gel and glass fiber mat composite, and then silica gel is dried by supercritical drying to obtain aerogel, thereby obtaining aerogel glass fiber mat thermal insulation layer 11. Various properties of the thermal insulation layer 11 are tested, and the results are shown in Table 2.

[0070] The ingredients of each embodiment and comparative example are shown in Table 1:

[0071] Table 1: Insulation material composition

[0072]

[0073]

[0074] Table 2: Thermal insulation layer performance test results

[0075]

[0076] From the data in Table 2, it can be seen that compared with the thermal insulation layer 11 without the endothermic material 103, the thermal conductivity of the thermal insulation layer 11 at room temperature (25°C) is higher after the endothermic material 103 is added. This is because the thermal conductivity of the endothermic material 103 is greater than that of the insulation powder 102, and the thermal conductivity of the thermal insulation layer 11 is increased after mixing; but since the endothermic material 103 is a discontinuous phase in the thermal insulation layer 11, its effect on the thermal conductivity of the thermal insulation layer 11 is small, so that the thermal conductivity of the thermal insulation layer 11 containing the endothermic material 103 at 25°C is ≤0.04W / (m·K). It can be understood that the more endothermic material 103 is added, the higher the thermal conductivity of the thermal insulation layer 11; preferably, the thermal conductivity of the thermal insulation layer 11 at 25°C is ≤0.025W / (m·K); more preferably, the thermal conductivity of the thermal insulation layer 11 at 25°C is ≤0.020W / (m·K).

[0077] Furthermore, at high temperature (500°C), the heat absorbing material 103 has undergone an endothermic reaction and generated pores in the heat insulating layer 11. Since air is a poor conductor of heat, the pores can make the thermal conductivity of the heat insulating layer 11 at 500°C lower. Preferably, the thermal conductivity of the heat insulating layer 11 at 500°C is ≤0.035W / (m·K); more preferably, the thermal conductivity of the heat insulating layer 11 at 500°C is ≤0.031W / (m·K). In this way, the heat insulating element 1 can absorb heat in the low temperature section to reduce the heat transfer of the battery cell 2; and the heat insulating performance of the heat insulating element 1 in the high temperature section can be improved to delay the spread of thermal runaway of the battery cell 2.

[0078] In some embodiments, the heat insulating layer 11 may also include a flame retardant and / or a sunscreen to absorb part of the heat released by the combustion when the battery cell 2 explodes or burns, reduce the temperature of the combustible surface, effectively inhibit the generation of combustible gas, and prevent the spread of combustion. The flame retardant may include an inorganic flame retardant and / or an organic halogen-free environmentally friendly flame retardant; when the inorganic flame retardant and the organic halogen-free environmentally friendly flame retardant are mixed, the mass ratio of the inorganic flame retardant to the organic halogen-free environmentally friendly flame retardant is 0.1:1 to 100:1. Among them, the inorganic flame retardant may include one or more of magnesium hydroxide, aluminum hydroxide, zinc borate, ammonium polyphosphate, red phosphorus, antimony oxide, and molybdenum compounds; the organic halogen-free environmentally friendly flame retardant may include one or more of polyphosphate, melamine, tris (1-oxo-1-phospha-2,6,7-trioxabicyclo [2,2,2] octane-4-methylene) phosphate, N, N-p-phenylenediamine (2-hydroxy) dibenzylphosphonic acid tetraethyl ester, melamine phosphate or melamine cyanuric acid. The sunscreen may include boron carbide (B4C), diatomaceous earth, manganese ferrite, MnO, NiO, SnO, Ag2O, Bi2O3, carbon black, graphite, titanium oxide, iron titanium oxide, aluminum oxide, zirconium silicate, zirconium oxide, iron (II) oxide, iron (III) oxide, manganese dioxide, iron titanium oxide (ilmenite), chromium oxide, carbide (such as SiC, TiC or WC) or a mixture thereof.

[0079] See also Figure 3 , Figure 3 A schematic diagram of the structure of the heat insulation element provided in one embodiment of the present application. In this embodiment, the heat insulation element 1 may further include a heat absorption layer 12, and the heat absorption layer 12 is arranged on two opposite surfaces of the heat insulation layer 11. When the battery cell 2 undergoes battery expansion or thermal runaway, the heat absorption material 103 in the heat absorption layer 12 undergoes an endothermic reaction to absorb heat, so as to reduce the transfer of heat to the heat insulation layer 11 and the adjacent battery cell 2 or the battery housing 3. In addition, the volume loss and gas volatilization of the heat absorption material 103 during the endothermic reaction will cause the volume of the heat insulation element 1 to decrease, providing expandable space for the battery cell 2 in thermal runaway, meeting the space requirements for thermal expansion of the battery, effectively buffering the expansion force of the battery, and improving the safety of the battery. In this embodiment, the heat absorption layer 12 and the heat insulation layer 11 can be compounded by gluing; in other embodiments, the heat absorption layer 12 and the heat insulation layer 11 can also select different compounding methods according to the specific battery model, which is not limited here.

[0080] like Figure 3As shown, the thermal insulation element 1 may further include a packaging layer 13, which covers the thermal insulation layer 11 and the heat absorption layer 12 to prevent the thermal insulation element 1 from breaking and falling into powder during transportation and use, thereby increasing the service life of the thermal insulation element 1. Specifically, the packaging layer 13 includes a packaging material, which may include a reflective film or an organic film or a non-woven fabric, or a high-silicon oxide fabric. The reflective film is one of aluminum foil and copper foil to effectively reduce heat transfer; the organic film is one of PET, PI, PE, PEEK, and PTFE films.

[0081] An embodiment of the present application provides a thermal insulation element 1, which includes a thermal insulation layer 11, and the thermal insulation layer 11 includes short-cut fibers 101 and thermal insulation powder 102. The thickness of the thermal insulation layer 11 is ≤10 mm to meet the requirements of high energy density and high volume assembly rate of the battery; the thermal conductivity of the thermal insulation layer 11 at 25°C is ≤0.04W / (m·K) to prevent heat transfer between battery cells 2 or heat transfer from the battery cell 2 to the battery shell 3; the thermal conductivity of the thermal insulation layer 11 at 500°C is ≤0.06W / (m·K) to prevent a battery cell 2 from transferring heat to an adjacent battery cell 2 or battery shell 3 when the battery bulging stage or thermal runaway stage occurs in a battery cell 2, thereby effectively delaying the spread of thermal runaway of the battery. In addition, compared with the prior art that uses long fibers as reinforcing fibers, the present application uses shorter chopped fibers 101 as reinforcing fibers, which is beneficial to evenly mix the reinforcing fibers and the insulating powder 102, thereby improving the thermal insulation performance of the insulating element 1; at the same time, the chopped fibers 101 can also provide mechanical reinforcement for the insulating powder 102, so that the insulating element 1 made of the chopped fibers 101 and the insulating powder 102 has a certain molding strength.

[0082] See also Figure 4 , Figure 4A simplified structural diagram of a battery provided in one embodiment of the present application. This embodiment provides a battery that can be used to provide power for an automobile; the battery includes a battery cell 2, a thermal insulation element 1, and a shell 3. Among them, the thermal insulation element 1 is the thermal insulation element 1 involved in any of the above embodiments, and the structure and function of the battery cell 2 are the same or similar to the battery cell 2 in the prior art, which will not be repeated here; multiple battery cells 2 are arranged in the shell 3 to prevent the external environment from causing damage to the battery cell 2. Specifically, the thermal insulation element 1 can be arranged between adjacent battery cells 2 to reduce heat transfer between adjacent battery cells 2 and effectively delay the spread of thermal runaway of the battery cell 2; the thermal insulation element 1 can also be arranged between the battery cell 2 and the shell 3 to reduce heat transfer from the battery cell 2 to the shell 3. In a specific embodiment, the battery may further include an exhaust valve (not shown) and / or a drain valve (not shown); wherein the exhaust valve is connected to the thermal insulation element 1, and is used to discharge the gas generated by the endothermic reaction of the endothermic material 103 in the thermal insulation element 1; the drain valve may also be connected to the thermal insulation element 1, and is used to discharge the liquid generated when the endothermic material 103 in the thermal insulation element 1 undergoes a phase change.

[0083] It will be apparent to those skilled in the art that the present application is not limited to the details of the exemplary embodiments described above, and that the present application can be implemented in other specific forms without departing from the spirit or essential features of the present application. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the present application is defined by the appended claims rather than the above description, and it is intended that all changes within the meaning and scope of the equivalent elements of the claims be included in the present application. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.

[0084] The above description is only an implementation method of the present application, and does not limit the patent scope of the present application. Any equivalent structure or equivalent process transformation made using the contents of the present application specification and drawings, or directly or indirectly used in other related technical fields, are also included in the patent protection scope of the present application.

Claims

1. A heat insulation element, characterized in that: It comprises a heat insulation layer, which comprises chopped fibers and heat insulation powder, wherein the thickness of the heat insulation layer is ≤10 mm, the thermal conductivity of the heat insulation layer at 25° C. is ≤0.04 W / (m·K), and the thermal conductivity of the heat insulation layer at 500° C. is ≤0.06 W / (m·K).

2. The thermal insulation element according to claim 1, characterized in that The heat-insulating layer further comprises a heat-absorbing material, and the heat-absorbing material is evenly dispersed in the gaps and / or surfaces of the chopped fibers and the gaps and / or surfaces of the heat-insulating powder.

3. The thermal insulation element according to claim 2, characterized in that The endothermic material can undergo an endothermic reaction after reaching an endothermic reaction starting temperature, and the endothermic reaction starting temperature is 70°C-300°C.

4. The thermal insulation element according to claim 3, characterized in that The endothermic material can experience volume loss and gas volatilization during the endothermic reaction.

5. The thermal insulation element according to claim 3, characterized in that After the endothermic reaction of the endothermic material occurs, the porosity of the heat insulation layer is 10%-80%, and the density of the heat insulation layer is 0.9g / cm 3 -2.5g / cm 3 .

6. The thermal insulation element according to claim 2, characterized in that The volume of the heat absorbing material accounts for ≤80% of the total volume of the chopped fibers, the heat insulating powder and the heat absorbing material.

7. The heat insulation element according to any one of claims 2 to 6, characterized in that: The endothermic material includes a phase change material and / or two or more materials capable of undergoing an endothermic reduction reaction.

8. The thermal insulation element according to claim 7, characterized in that The phase change material includes inorganic phase change material and / or organic phase change material; preferably, the inorganic phase change material includes one or more of inorganic hydrated salts, carbonates, bicarbonates, and hydroxides; preferably, the inorganic phase change material includes one or more of sodium bicarbonate, ammonium aluminum sulfate dodecahydrate, magnesite, calcium sulfate dihydrate, potassium carbonate, aluminum hydroxide, aluminum oxide hydroxide, and magnesium hydroxide; preferably, the organic phase change material includes one or more of paraffin, fatty acids, and fatty alcohols.

9. The thermal insulation element according to claim 7, characterized in that The two or more materials capable of undergoing endothermic reduction reaction include iron oxide and activated carbon and a sodium carbonate catalyst.

10. The heat insulation element according to any one of claims 2 to 6, characterized in that: The heat insulating layer is prepared by uniformly mixing the chopped fibers, the heat insulating powder and the heat absorbing material and then pressing and molding the mixture.

11. The thermal insulation element according to claim 1, characterized in that The heat-insulating layer further comprises a flame retardant and / or a sunscreen.

12. The thermal insulation element according to claim 1, characterized in that The heat insulating element further includes a heat absorbing layer, which is disposed on at least one of two opposite surfaces of the heat insulating layer.

13. The thermal insulation element according to any one of claims 1 to 6, 11 or 12, characterized in that: The heat insulation element further comprises a packaging layer, wherein the packaging layer covers the heat insulation layer or covers the heat insulation layer and the heat absorption layer.

14. A battery, characterized in that: include: case; One or more battery cells disposed within the housing; The thermal insulation element according to any one of claims 1 to 13; The heat insulating element is arranged between adjacent battery cells, and / or the heat insulating element is arranged between the battery cells and the housing.

15. The battery according to claim 14, characterized in that The battery further comprises an exhaust valve and / or a liquid discharge valve, and the exhaust valve and / or the liquid discharge valve are connected to the heat insulation element.

Citation Information

Cited By

  • Graphite-PTFE composite film capable of adaptively switching heat transfer resistance along with temperature

    CN120206908A